2021
DOI: 10.1186/s13054-021-03660-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a restrictive antibiotic policy on the acquisition of extended-spectrum beta-lactamase-producing Enterobacteriaceae in an endemic region: a before-and-after, propensity-matched cohort study in a Caribbean intensive care unit

Abstract: Background High-level antibiotic consumption plays a critical role in the selection and spread of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-E) in the ICU. Implementation of a stewardship program including a restrictive antibiotic policy was evaluated with respect to ESBL-E acquisition (carriage and infection). Methods We implemented a 2-year, before-and-after intervention study including all consecutive adult patients admi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…The overall prevalence of ESBL-E rectal carriage in pets (4.7%, 95% CI: 2.1–9.1) was moderate, in agreement with observations of fecal carriage among pigs (7.3%), beef cattle (14.7%) and humans (4.4%) in Guadeloupe ( Gruel et al, 2021 ; Le Terrier et al, 2021 ). The prevalence of ESBL-E carriage was in the range observed worldwide (average, 6.9%) in a meta-analysis, the highest level being reported in dogs in Africa (16.5%) and in cats in Asia (16.8%) ( Salgado-Caxito et al, 2021 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overall prevalence of ESBL-E rectal carriage in pets (4.7%, 95% CI: 2.1–9.1) was moderate, in agreement with observations of fecal carriage among pigs (7.3%), beef cattle (14.7%) and humans (4.4%) in Guadeloupe ( Gruel et al, 2021 ; Le Terrier et al, 2021 ). The prevalence of ESBL-E carriage was in the range observed worldwide (average, 6.9%) in a meta-analysis, the highest level being reported in dogs in Africa (16.5%) and in cats in Asia (16.8%) ( Salgado-Caxito et al, 2021 ).…”
Section: Discussionsupporting
confidence: 84%
“…Data on resistance to antibiotics in Guadeloupe are scarce and recent. The University Hospital of Guadeloupe faced the emergence of carbapenemase-producing Enterobacteriaceae isolates and a very high incidence of nosocomial ESBL-E infections ( Bastian et al, 2015 ; Breurec et al, 2015 ; Le Terrier et al, 2021 ). A moderate prevalence of ESBL-E (around 5%) was observed in studies on community human urinary tract infections ( Guyomard-Rabenirina et al, 2016 ), on fecal carriage by domestic animals and livestock ( Gruel et al, 2021 ) and on wild fauna ( Guyomard-Rabenirina et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, ICUs are among the heaviest consumers of antibiotics, with an estimated 70% of patients receiving antibiotics during an ICU stay ( 7 ). Various observational and before-after studies show that duration of antibiotic therapy is linked to antibiotic resistance development, both in ICU ( 17 , 18 ) and non-ICU ( 19 21 ) settings. A number of randomized trials have shown that targeted interventions can safely reduce the ABTD in ICU ( 11 , 22 , 23 ) or non-ICU ( 9 , 10 , 12 , 13 ) patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the recent surviving sepsis campaign guidelines, in adults with possible sepsis and not in shock, a time-limited, rapid investigation is advised [ 16 ]. Moreover, recent studies have shown that an antibiotic stewardship program that initiates antibiotic therapy only after microbiological identification, except for septic shock or severe ARDS, is safe [ 17 ]. As evidenced, mPCR results were obtained a couple of hours after sampling; therefore, intensivists could wait for such results to optimize antibiotic prescription.…”
Section: Discussionmentioning
confidence: 99%